HEB831749_Supplemental_Appendix_1 – Supplemental material for Health Promotion Interventions in Sports Clubs: Can We Talk About a Setting-Based Approach? A Systematic Mapping Review ... - Geidne, Susanna; Kokko, Sami; Lane, Aoife; Ooms, Linda; Vuillemin, Anne; Seghers, Jan; Koski, Pasi; Kudlacek, Michal; Johnson, Stacey; Hoye, Aurélie Van (SAGE Journals, 2019)
Supplemental material, HEB831749_Supplemental_Appendix_1 for Health Promotion Interventions in Sports Clubs: Can We Talk About a Setting-Based Approach? A Systematic Mapping Review by Susanna Geidne, Sami Kokko, Aoife Lane, Linda Ooms, Anne Vuillemin, Jan Seghers, Pasi Koski, Michal Kudlacek, Stacey Johnson and Aurélie Van Hoye in Health Education & Behavior ...